A Clinical Evaluation Denture Adhesives Used by Patients With Xerostomia. Issue 7 (February 2015) - Bogucki, Zdzislaw A.; Napadlek, Piotr; Dabrowa, Tomasz
Abstract : Abstract: The purpose of study was to analyze the participants' opinions concerning the effectiveness of 6 denture adhesives (DA). The study group included 60 participants. Criteria for selecting the patients were as follows: reduced retention and stabilization of maxillary complete dentures and xerostomia. These features were evaluated on basis of clinical examination and standard sialometry tests (u-SFR). Retention of maxillary dentures was scored by modified Kapur index before application of DA. All participants were divided randomly into 6 groups regarding the use of the 6 DA during a 6-month period. After this time, participants completed an HRQL questionnaire. DA noticeably improved retention and stabilization of maxillary complete dentures. DA in the glue form had the best retention effectiveness in participants with xerostomia. These materials are difficult to clean from the denture base. The data are presented in tables and figures. The results of the study collected positive influence of adhesives on retention of dentures in xerostomia patients. The cleaning dentures and denture bearing tissues was difficult. DA help in the use of prostheses, but it is also necessary for the treatment of the causes and symptoms of xerostomia.